CompTIA RFID+ : - Sweeney, Patrick J. (Wiley Pub., 2007)
This comprehensive study guide thoroughly covers the CompTIA RFID+ exam, the only certification offered for radio frequency identification (RFID), the technology that is rapidly gaining popularity and is expected to completely replace bar codes. Your study will focus on interrogation zone basics, testing and troubleshooting, standards and regulations, tag knowledge, design selection, installation, site analysis, RF physics, and RFID peripherals. The accompnaying CD-ROM provides two bonus exams, a detailed glossary of terms, and a searchable PDF of the book.